Transformative coping and spirituality: The case of the Kakure Kirishitan during the Tokugawa period - Chong, Xannon; Kimura, Kaori; Chong, Siaw Fung (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study explores the historical experiences and psychological resilience of the Kakure Kirishitan (Hidden Christians) during the Tokugawa period of Japan, focusing on their coping strategies during religious persecution. The research aims to (1) understand the nature and impact of the Tokugawa regime’s suppression of Christianity and (2) analyse how the Kakure Kirishitan cope with the stress of oppression to preserve their faith by using the Transformative Coping Model (TCM). Methods: This study applies qualitative historical analysis by synthesising scholarly literature, primary accounts, and theoretical perspectives, especially those related to stress-coping, spirituality, and resilience. The geographical and historical focus is Japan between the 17th and 19th centuries, during which Christianity was outlawed. Findings: Findings reveal that the Kakure Kirishitan employed various creative and spiritual coping mechanisms, including religious syncretism, oral transmission, symbolic secrecy, and ritual innovation. These strategies allowed them to maintain both their religious identity and communal cohesion in secret. Their use of encoded rituals and adapted theology illustrates how adversity was transformed into spiritual growth and cultural preservation. Despite psychological burdens such as fear and trauma, the Kakure Kirishitan interpreted suffering as divine testing, reinforcing their endurance across generations. Conclusion: This study concludes that the Kakure Kirishitan’s survival reflects the core principles of transformative coping—meaning-making, creativity, and collective resilience—as they shaped a unique spiritual identity under prolonged oppression. Novelty/Originality of this article: This study offers a novel contribution by linking the historical experience of the Kakure Kirishitan with the Transformative Coping Model (TCM), a framework rarely applied in historical religious studies.